Comparative Test of Ovaprim, Spawnprim, and HCG in the Process Spawning of Pangasianodon hypophthalmus - Leonita, Vinka; Utomo, Deny Sapto Chondro; Fidyandini, Hilma Putri (Jurnal Perikanan dan Kelautan, 2021)
Pangasianodon hypophthalmus is a type of freshwater fish that has potential and has economic value. Its production target which increases every year causes farmers to spawn with the help of hormonal stimulation. The aimed of this research was to test and find out the results of the use of three different hormones namely Ovaprim, Spawnprim, and HCG in P. hypopthalmus spawning. This research was conducted in January 2020 at the Trimurjo Fish Seed Center, Central Lampung. This research used a randomized complete design method with the 3 treatments, P1 (Ovaprim 0,5 ml / kg), P2 (Spawnprim 0,5 ml / kg), P3 (HCG 500 IU / kg) and 3 replications. The results of this research indicate a significant difference (p <0,05) in the relative fecundity parameters, fertilization rate, and hatching rate, but not significantly different in the parameters of latensi periode and diameter of eggs. In P1, Ovaprim hormone injections provide better reproductive performance compared to Spawnprim and HCG injections.